Impact of board structure on firm performance: evidence from an emerging economy - Qaiser Rafique, Yasser; Abdullah, Al Mamun; Rodrigs, Marcus (Emerald Group Publishing Ltd., 2017)
Purpose: The aim of this paper is to examine the association between board demographics and firm financial performance of Karachi Stock Exchange companies and describe the attributes of these firms and their boards. The connection between board structure and firm performance has attracted much attention, especially in emerging economies, yet yielded many inconsistent empirical results. Design/methodology/approach: This study examines the relationship between board structure and the performance of Pakistani public listed companies by using a sample of Karachi Stock Exchange 100 (KSE-100) indexed companies. This study exploits the corporate performance by accounting-based measures (return on assets), market-based measures (Tobin’s Q), and economic profit (economic value added). Findings: The outcome of the study shows the positive relationship between the board size, minority representation in board, and family director’s in-board and firm performance. The authors also find that, instead of adding value, independent directors in Pakistan are negatively associated with firm value. Research limitations/implications: The study is based on KSE-100 indexed companies from 2009 to 2013; however, a large sample and multiple years’ data are required. Practical implications: The paper provides empirical evidence that board independence is not necessary for public-listed companies in Pakistan and would be of interest to regulatory bodies, business practitioners, and academic researchers. Originality/value: The paper contributes to the literature on corporate governance and firm performance by introducing a framework for identifying and analyzing moderating variables that affect the relationship between board structure and firm performance. © 2017, © Emerald Publishing Limited.